Geographical variation in compulsory hospitalisation - ethical challenges - Tore Hofstad; Tonje Lossius Husum; Jorun Rugkåsa; Bjørn Morten Hofmann (BMC, 2022)
Abstract Background Compulsory hospitalisation in mental health care restricts patients' liberty and is experienced as harmful by many. Such hospitalisations continue to be used due to their assumed benefit, despite limited scientific evidence. Observed geographical variation in compulsory hospitalisation raises concern that rates are higher and lower than necessary in some areas. Methods/discussion We present a specific normative ethical analysis of how geographical variation in compulsory hospitalisation challenges four core principles of health care ethics. We then consider the theoretical possibility of a "right", or appropriate, level of compulsory hospitalisation, as a general norm for assessing the moral divergence, i.e., too little, or too much. Finally, we discuss implications of our analysis and how they can inform the future direction of mental health services.